Institutions and Economic Development: Methodological Analysis of Timur Kuran's Approach to Islamic Economics - Levent, Adem (ILEM, 2019)
Timur Kuran is an important theorist who criticizes Islamic economics. In the majority of Kuran's studies, he discusses whether Islamic economy discourse founds itself on a realistic ground, He claims that Islamic economics does not have a coherent theory and that Islamic law has left the Middle East economically back. While researching about Islamic economics and the development of the Middle East, he has been attempting to associate economics in general and Islamic economics in particular, with elements such as non-economic law, morality, and identity. The basic methodology of Kuran draws attention to institutional economics, which attempts to analyze economic activities through institutional social structures. Kuran attempts to account Islamic economics and the economic development process of the Middle East by employing the institutional economic framework. However, the main problem in his analysis is that both institutional and Islamic economics as well as the Middle Bast's development process are evaluated according to the conclusions that Orthodox economics will accept, not in terms of their own existence. Kuran's critique of Islamic economics is also similar to the criticisms that Orthodox economists have directed particularly to institutional economics, and heterodox economics in general. In this respect, many of Kuran's critiques of Islamic economics are also the problems of modern orthodox economics, and the same criticisms apply to modern economics. The formalist economic discourse which escapes from reality, the free rider problem, the market failure theory are the major problems facing modern economics, and these are not solely the problems of Islamic economics. Therefore, it is not appropriate to criticize Islamic economy discourse over these problems.
Keywords: Islamic economics; institutional economics; institutions; law; methodology